Prevalence of Malocclusion and Treatment Needs among School Children in Urban Areas of Pakistan. - Yousaf, Iqra; Hashmi, Gulsana; Bano, Aisha; Naseem, Hina Naz; Tariq, Noman; Akhtar, Fahmeed; Naeem, Nabiha (Journal of Neonatal Surgery, 2025)
Background: Malocclusion is a prevalent childhood oral health issue which may influence the mastication, speech, esthetic appearance and psychosocial well-being. Having the capability to identify and treat early is a significant aspect toward avoiding complications in the long term. Aim: To identify the level of malocclusion and the orthodontic treatment requirement of school children. Methods: The study used a cross-sectional survey to sample 380 school children aged between 6-15 years. Multistage random sampling of public and private schools was used to select the participants. Clinical evaluation of malocclusion was determined by the Dental Aesthetic Index (DAI) and treatment requirements were determined by the Index of Orthodontic Treatment Need (IOTN). The data were examined using SPSS v24 and the associations were checked with Chi-square tests, and p < 0.05 was regarded as significant. Results: The prevalence of malocclusion was found to be 63.2 with Class I malocclusion being the most prevalent (34.2%), then Class II (18.4%), and Class III (10.5%). The occurrence of normal occlusion was 36.8. The need of orthodontic treatment was moderate in 34.2% and definite in 28.9% of respondents. Conclusion: Malocclusion is very common among school children and significant number of them need orthodontic treatment. It is suggested to use early screening and preventive programs in school to make sure that the disease is detected and controlled timely, enhancing the oral health, aesthetics and life quality..